Pengelolaan Surat Menyurat Bagian Umum Sekretariat Daerah Kabupaten Labuhanbatu - Putri Apriani Batubara; Mutiara Khinaya; Zainartit Zainartit (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Correspondence services are an important part of the administration at the Labuhanbatu regent's office. Currently, the Labuhanbatu regent's office uses Ms. Word for its letter writing system. This method is very simple and of course has weaknesses, one of which is that you have to search for mail files in certain folders, and often you lose some files/folders which requires a system to make correspondence services easier. So far, administration and correspondence services have been carried out using a conventional system, namely using Microsoft Word with a pre-existing letter format or done manually. Generally, each letter has a different writing format depending on the purpose of the letter itself. In the conventional system, if we want to write a letter in a certain format, then we have to look for a sample letter then rewrite the writing format, and we write the letter in a certain format. Because it takes a long time to process the letter and can cause loss of letter format files because there are several file folders. In this research, we will provide solutions on how to make letters more modern and faster. This information system serves 7 groups of letters, namely Dean's Decree, Cover Letter, Academic Atmosphere Form, Lecturer Employee Assignment Letter, etc., Invitation Letter, and Lecturer Assignment Letter to the Chancellor. This information system can be accessed by the regent's office admin and regent's office employees whose data has been recorded in the ledger/database. This system was created using the PHP programming language, Javascript, with the Bootstrap Framework, and MySQL as the Database Management System. In testing this system, the author used a manual method.